DISINFECTION PROPERTIES OF MODERN DISINFECTANTS AGAINST TRICHOSTRONGYLUS TENUIS NEMATODE EGGS - Starodub, Ye. (Scientific Progress & Innovations, 2021)
Invasions caused by nematodes parasitizing in the gastrointestinal tract of poultry, including trichostrongylosis, are quite widespread among goose helminthiases. Therapeutic and preventive measures must be performed taking into account the peculiarities of the life cycle of trichostrongyluses and be aimed at their effective destruction at different stages of development. The disinfection of poultry facilities is the most effective among them. The aim of the research was to establish the disinfection properties of modern disinfectants against the eggs of Trichostrongylus tenuis nematodes. Experimental testing of the following disinfectants in laboratory conditions at different exposures and concentrations was conducted: virosan (“BioTestLab” LLC, Ukraine), dezsan (“Brovapharma” LLC, Ukraine) and germecide-VS (“Vetsintez” LLC, Ukraine). The main indicator of the disinfectants action against nematode eggs was the value of their disinfection effectiveness. The results of the research revealed a high level of dezsan disinfection efficacy (94.87–100 %) against trichostrongyluses eggs in 1–2 % concentrations at exposures of 10, 30, and 60 min. When using 0.5 % of dezsan solution, its disinfection efficiency ranged from 49.35 to 85.47 % depending on the exposure. Virosan showed a high level of disinfection efficacy at a concentration of 0.25 % and exposure of 60 min (91.26 %) and at a concentration of 0.5 % and exposures of 10, 30, and 60 min (100 %). Unsatisfactory level of virosan disinfection effectiveness was manifested in 0.1 % concentration at exposures of 10 and 30 min (41.60– 53.63 %). This disinfectant at a concentration of 0.1 % (exposure of 60 min), 0.25 % (exposures of 10 and 30 min) showed a satisfactory level of disinfection effectiveness against nematode eggs (60.43–82.74 %). Germecide-VS showed a high level of disinfection efficacy (100 %) in concentrations of 0.25 % (exposures of 30 and 60 min) and 0.5 % (exposure of 10–60 min). Unsatisfactory level of disinfection efficacy (39.22– 52.02%) was detected at using of germecide-VS at a concentration of 0.1 % (exposure of 10 and 30 min), and satisfactory (63.06–84.63%) – at concentrations of 0.1 and 0.25 % and exposures of 60 and 10 min, respectively. The obtained data allow to recommend virosan, dezsan and germecide-VS disinfectants for disinfection of environmental objects and poultry premises in fighting and preventing of goose trichostrongylosis.